Eksplorasi Upaya Internasionalisasi Bahasa dan Budaya Indonesia Melalui Program BIPA - Astuti Simanullang; Azra Batrisyia; Ernisa Hidayah; Safinatul Hasanah Harahap (Journal on Education, 2024)
This research focuses on efforts to internationalize Indonesian language and culture through the BIPA program. As an official language regulated in Law No. 24/2009, Indonesian has an important role in strengthening Indonesia's position internationally. The purpose of this study is to explore the efforts that have become government initiatives in internationalizing Indonesian language and culture through the BIPA program. Based on qualitative research using the literature research method, the results show that there are four main strategies to internationalize the Indonesian language through the BIPA program, namely expanding the network of BIPA member organizations across national borders, incorporating Indonesian cultural content into the BIPA curriculum, incorporating Indonesian music into the BIPA curriculum, and providing UKBI training for foreigners who will work or study in Indonesia. In addition, this study also discusses BIPA development strategies related to international collaboration efforts, technology utilization, cultural promotion, teacher training, formation of internal committees, development of learning materials, increasing the number of resources, evaluation and research, and advocacy and promotion as tactics to develop and improve BIPA programs. It is expected that a strategic approach that takes into account these various aspects will increase the effectiveness of the BIPA program and strengthen the position of Indonesian in the international world.